Validation of a Questionnaire to Evaluate the Hotel Employee Innovation Competency: Confirmatory Factor Analysis - Iffah Rosyiana; Fendy Suhariadi; Seger Handoyo; Fajrianthi Fajrianthi (Universitas Ahmad Dahlan, 2020)
The development and growth of the hotel business in Indonesia are increasingly rapid, along with the development of the tourism industry. One of the competencies that are needed in facing business competition is innovative competency. Although there have been many studies discussing the importance of mastering innovative competencies, there are still limited instruments for measuring the innovative competencies of hospitality employees. The purpose of this study is to develop an innovative competency measurement instrument for hospitality employees. The development of an innovation competency instrument for hotel marketing employees consists of three indicators, namely individual, interpersonal, and social network conditions. Data collection involved 143 hospitality marketing employees. Data analysis to test the validity of this innovative competency questionnaire uses the Confirmatory Factor Analysis (CFA). The study results revealed that the questionnaire was valid with the following criteria: RMSEA 0.094 (moderate), RMR = 0.037 (fit), Comparative Fit Index (CFI) = 0.901 (fit), Tucker-Lewis Index (TLI) = 0.891 (moderate), and NFI = 0.837 (moderate). These results indicate that an indication of a good fit or an innovative competency construct model in this study is declared fit so that it can be used to identify the innovative competencies of Sales Marketing employees in hospitality.Keywords: innovative; interpersonal; social network; instrument validity.